An Android & IoT based Health Care and Personal Monitoring Device - V.Deshpande, Bhagyashree.; S Sannakki, Sanjeev (International Journal of Engineering and Technology, 2018)
The paper signifies the test to monitor the condition of diabetic patientâ€™s breath which involves non invasive medical treatment or test which does not involve cutting of the body or not penetrating any instruments which are harmful. This one is identified as quick and user friendly technique which diagnosis the diabetic ketoacidosis [DKA]. Basically DKA is preventable complication type 1 diabetic mellitus. Usually diabetic are required to undergo the urinary and blood glucose test to monitor the diabetic condition. So these methods are expensive, inconvenient and harmful. Keeping these things in mind recently a new technique has been involved in terms which is making use of breath acetone that has been considered as a new ketone indicator which is non painful convenient and it reflects the level of ketone in the body .In this research we are providing a method to monitor the ketone level by using the measurement of breath. We are mainly focusing on easy handheld way for health care on monitoring the diabetic level with using the breath. We are using Internet of Things (IoT) system to provide the facility to the patients for diagnosis and self monitoring component which sense the breath ketone and help us to see the reading for further diabetic treatmentÂ Â